Implanting a posterior chamber phakic intraocular lens in highly myopic eyes with peripheral primary iris and ciliary body cysts. Issue 2 (March 2019) - Zhao, Jing; Luo, Dongqiang; Sun, Yong; Niu, Lingling; Zhao, Feng; Wang, Xiaoying; Wang, Hua; Chen, Qian; Zhou, Xingtao
Purpose: To investigate the safety and efficacy of implanting a posterior chamber implantable collamer lens with a central hole in cases of high myopia with peripheral primary iris or ciliary body cysts. Methods: A total of 37 eyes of 19 patients with primary iris or ciliary body cysts detected by ultrasonic biological microscope were included, with spherical powers of −10.26 ± 3.28 D and cylinder powers of −1.71 ± 1.18 D. Each patient received ultrasonic biological microscope and a routine examination before implantation of the implantable collamer lens. A routine postoperative follow-up was performed to observe changes in the iris or ciliary body cyst, ranging from 3 to 18 months. Results: There were no complications. At the last follow-up, 56.8% (21/37) of eyes achieved the same corrected distance visual acuity as their preoperative measurements, 43.2% of eyes were enhanced by ≥1 line, and no patients' corrected distance visual acuity declined. The efficacy index and safety index were 0.95 and 1.11, respectively. After 18 months, 66.7% of the spherical equivalents were between ±0.5 D with 100% between ±1.0 D. The postoperative mean spherical equivalents at 1, 3, 6, 12, and 18 months were −0.45 ± 0.31 D, −0.39 ± 0.29 D, −0.36 ± 0.30 D, −0.39 ± 0.38 D, and −0.48 ± 0.23 D (p = 0.789). The vaults were 516 ± 140, 548 ± 124, 498 ± 133, 582 ± 161, and 557 ± 110 μm (p = 0.355). There were no changes in size (p > 0.05), number, or position of the iris or ciliary body cysts. Conclusion: Implantable collamer lens implantation is safe and effective for highly myopic patients with peripheral primary iris and ciliary body cysts. The cysts did not change after operation in this study.